REVIEW OF THE BALANCED SCORECARD IMPLEMENTATION IN HEALTH SECTOR ORGANIZATION - Silvia Tarigan; Adang Bachtiar (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Several studies reported that performance measurement using balanced scorecard is better than using traditional performance measurements. Balanced scorecard approach has been used in many health service sectors, both profit and non-profit, including hospitals, health service system, center for mental health, pharmacy services and health insurance company. Thisstudy aims to review the balanced scorecard implementation in health sector organization of the published literature from 2012 to 2019. Methods: This study was used literature review method by collecting data of the Balanced Scorecard in the health care sector and draws on the 6 years of published literature to January 2019. The literature were found from a search on Google Scholar as well as Thomson Reuters Web of Knowledge. The search terms were used “Balanced Scorecard”, “Health Balanced Scorecard” and “BSC” on English language only. The papers were classified by topics, research settings and research methods and data analysis techniques. Results: From 1465 papers were examined, 12 pieces of literature met inclusion criteria. From 12 pieces of literature have been reviewed, were used case study research method, eleven papers with qualitative research and one paper using the Delphi method. Based on 12 papers found that The balanced scorecard in health sector organization has been implemented in ICO, primary health care, hematology department, hospitals, home care nursing, health facilities, health systems, nutritional therapy company and clinical nutrition. Moreover, the Balanced Scorecard approach was used for health service budgeting, developing key performance indicators, improving hospital performance, assessing the baseline status, as an indicator in conducting evaluations. Conclusion: This study found that several studies consistently proved that Balanced scorecard is essential for performance and evaluation measurement in the health sector. Keywords : Balanced Scorecard, , performance measurement, health care, health services